Facile synthesis and characterization of novel dicarboxylate-Cu based MOFs materials - Sherino, Bibi; Halim, Siti Nadiah Abdul; Manan, Ninie Suhana Abdul; Sarip, Rozie; Al'Abri, Aisha Mohammed; Mohamad, Sharifah (Elsevier, 2019)
This work describes the synthesis and characterization of benzylimidazole (Bim) and piperazine (P) based metal organic framework (MOF) materials with two different linkers of adipic acid (A) and terephthalic acid (T) namely: ABim-Cu-MOF, TBim-Cu-MOF, AP-Cu-MOF, and TP-Cu-MOF. The physical and chemical characterization of these MOF materials were studied by elemental analysis (CHN), Fourier-transform infrared spectrometry (FT-IR), powder x-ray diffraction (PXRD), BET surface area and thermogravimetric analyses. The synthesized MOF materials were used as a modifier for carbon paste electrode to study its electrochemical behaviour towards ferricyanide. The electrochemical characterization revealed that the newly synthesized MOFs offer an excellent potential as electrode modifier for the redox reaction of ferricyanide. The reaction was reversible and diffusion controlled with the calculated diffusion coefficient values in the range of (4.86 × 10−5–2.66 × 10−5 cm2 s−1). © 2019 Elsevier B.V.